P‐44: Long Lifetime and High Performance OLED Display with Wide Temperature Range for Automotive Application. Issue 1 (29th May 2019) - Mizusaki, Masanobu; Shibasaki, Masakazu; Tsuchiya, Hiroshi; Tsukamoto, Yuto; Umeda, Tokiyoshi; Nakamura, Kei; Ohshita, Toshiaki; Shimada, Shinji
Abstract : We have developed a long lifetime OLED display by optimizing each organic layer materials. The lifetime of the new developed blue OLED under 50 mA/cm 2 driving at 85 °C was improved more than four times compared with the previously developed OLED, and achieved longer than 1, 500 hours in a real use. The developed OLED display would be useful for automotive application.